Capturing the Women's Army Corps : The World War II Photographs of Captain Charlotte T. McGraw - Bonnell, Françoise Barnes, 1962- (Book collections on Project MUSE., 2013)
The photographs taken by Charlotte T. McGraw, the official Women's Army Auxiliary Corps (WAAC) photographer during World War II, offer a comprehensive visual record of the approximately 140,000 women who served in the U.S. Army during the war. This collection of 150 of McGraw's photos includes pictures made in Africa, in England at the headquarters of the European Theater of Operations, in Asia and the Pacific, and in military hospitals in the United States. A former Metro-Goldwyn-Mayer camera operator and the only assigned WAAC photographer, McGraw personally handled the release of 73,660 photos used extensively for recruiting posters and publicity. Her photographs were published in the New York Times, New York Herald Tribune, and used by the Associated Press and the United Press, as well as in recruiting posters, handouts and informational pamphlets, and in the most popular magazines of the era such as Time, Colliers, Women's Home Companion, Parade, Saturday Evening Post, and Mademoiselle. -- Provided by publisher.